Analisis Yuridis Pelaksanaan Penggantian Antar Waktu (Paw) Anggota Dprd Provinsi Daerah Istimewa Yogyakarta - Anik Tri Haryani; Retno Iswati; Muhammad Candra Wijaya (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
Abstract-This research was made with the aim of examining the law relating to the implementation of recall for members of the DPRD in the Special Region of Yogyakarta. Recall is regulated in Act Number 17 year 2014 about People's Consultative Assembly, the People's Representative Council, the Regional People's Representative Council. This research studied about suitability of recall implementation with the regulations and the impact on democratic system in Indonesia as a result of recall by members of the DPRD in Special Region of Yogyakarta. The author uses empirical legal research by collecting results from observations and data which supported by interviews with informants. In addition, the author is guided by the rules / regulation in Indonesia. The results of this research are the recall members of the DPRD Yogyakarta have a suitability with Act Number 17 year 2014 about People's Consultative Assembly, the People's Representative Council, the Regional Representative Council and the Regional People's Representative Council. However, the implementation of recall in accordance with these regulations cannot prevent political parties from taking their right to do recall for personal interests of the political parties.